Silencing of the Mitogen-Activated Protein Kinases (MAPK) Fus3 and Slt2 in Pseudocercospora fijiensis Reduces Growth and Virulence on Host Plants - Onyilo, Francis; Tusiime, Geoffrey; Tripathi, Jaindra N.; Chen, Li-Hung; Falk, Bryce; Stergiopoulos, Ioannis; Tushemereirwe, Wilberforce; Kubiriba, Jerome; Tripathi, Leena (Frontiers in Plant Science, 2018)
Pseudocercospora fijiensis, causal agent of the black Sigatoka disease of Musa spp., has spread globally since its discovery in Fiji 1963 to all the banana and plantain growing areas across the globe. It is becoming the most damaging and economically important disease of this crop. Identification and characterisation of genes that regulate infection processes and pathogenicity in P. fijiensis will provide important knowledge for the development of disease resistant cultivars. In many fungal plant pathogens, the Fus3 and Slt2 are reported to be essential for pathogenicity. Fus3 regulates filamentous-invasion pathways including formation of infection structures, sporulation, virulence, invasive and filamentous growth, whereas Slt2 is involved in the cell wall integrity pathway, virulence, invasive growth, and colonisation in host tissues. Here, we used RNAi-mediated gene silencing to investigate the role of the Slt2 and Fus3 homologues in P. fijiensis in pathogen invasiveness, growth and pathogenicity. The PfSlt2 and PfFus3 silenced P. fijiensis transformants showed significantly lower gene expression and reduced virulence, invasive growth and lower biomass in infected leaf tissues of East African Highland Banana (EAHB). This study suggests that Slt2 and Fus3 MAPK signalling pathways play important roles in plant infection and pathogenic growth of fungal pathogens. Silencing of these vital fungal genes through host-induced gene silencing (HIGs) could be an alternative strategy for developing transgenic banana and plantain resistant to black Sigatoka disease.